EHMT1 binds to NF-κB p50 and represses gene expression. - Ea, C.K.; Hao, S.; Yeo, K.S.; Baltimore, D. (American Society for Biochemistry and Molecular Biology, 2012)
Transcriptional homeostasis relies on the balance between positive and negative regulation of gene transcription. Methylation of histone H3 lysine 9 (H3K9) is commonly correlated with gene repression. Here, we report that a euchromatic H3K9 methyltransferase, EHTM1, functions as a negative regulator in both the NF-κB- and type I interferon-mediated gene induction pathways. EHMT1 catalyzes H3K9 methylation at promoters of NF-κB target genes. Moreover, EHMT1 interacts with p50 and, surprisingly, p50 appears to repress the expression of type I interferon genes and genes activated by type I interferons by recruiting EHMT1 to catalyze H3K9 methylation at their promoter regions. Interestingly, we find that absence of EHMT1 licenses TNFα to stimulate induction of IFNβ indicating that EHMT1 is required for establishing the signal-specific induction of IFNβ. Silencing the expression of EHMT1 by RNA interference enhances expression of a subset NF-κB regulated genes, augments interferon production and augments antiviral immunity. Our findings establish a H3K9 methyaltion-mediated regulation of the immune response.